Structural and transport characterization of ultra thin Ba0.05Sr0.95TiO3 layers grown over Nb electrodes for the development of Josephson junctions - Sirena, Martin (2012)
A phenomenological approach was used to obtain critical information about the structure and electrical properties of ultra thin Ba0.05Sr0.95TiO3 (BSTO) layers over Nb electrodes. The method allows, in a simple way, to study and to optimize the growth of the barrier in order to improve the performance and application of Josephson junctions. A very good control of the layer thickness with a low roughness was achieved during the deposition process. The BSTO layers present an energy barrier of 0.6 eV and an attenuation length of 0.4 nm, indicating its good insulating properties for the development of Josephson junctions with improved performance.